Prevalence of Leptospira serovar Hardjo and risk factors in smallholder dairy cattle in Tanzania - Motto, Shabani K.; Shirima, G.M.; Bronsvoort, B.M. de C.; Cook, Elizabeth A.J. (International Livestock Research Institute, 2024)
Key messages High Leptospira seroprevalence, particularly in a few regions. Farmer training required to minimize animal and public health risks associated with animal husbandry practices. Further research on circulating serovars to target interventions particularly vaccination efforts.